Intemporal Futura - Santos, Tiago José Miranda (2019)
Futura is one of the best-known typefaces in the world. We can recognise its shapes even without being aware of its existence as we are submerged by marketing communication either through online or offline channels used by world-renowned brands like OMEGA, Nike or Absolut Vodka. From watches to sneakers and vodka, Futura has been omnipresent in visual communication.1It is probably the most successful heir of modern-ism, being present on a wide range of mediums and typographic weights without losing its formal characteristics